Web-Based Sales Information System in One of The Cash Shops Using the Business to Customer Method - Nurmaidah Febrica Waruwu; Hasanah Tisna Amijaya (LPPM STMIK Mardira Indonesia, 2023)
Science and information technology's rapid and sophisticated progress motivates humans to generate novel solutions that facilitate easy and speedy information acquisition. Consumer behavior has experienced a substantial transformation in the present digital age. Many people opt for Internet purchasing due to the ease, accessibility, and flexibility it provides. The fashion industry is not immune to this phenomenon, as internet retailers are gaining popularity as a preferred method for buying clothing and accessories. Online retailers offer advantages such as convenient access to product catalogs, the ability to purchase at any time and from any location, and a broader selection of options. This offers a substantial opportunity for fashion retailers to access a larger pool of potential customers and enhance their market dominance. The sales process in a particular fashion store now depends on a traditional system involving direct transactions at the physical store and maintaining sales data through paper documents. This technique encounters multiple impediments that must be surmounted. A significant challenge is the limited accessibility to clients beyond the geographical confines of the physical business. In addition, using paper documents to manage sales data also needs to be improved in efficiency and accuracy. The method is laborious and prone to human errors. As inferred from the background description, the author's objective is to develop a web-based sales information system for a fashion retailer utilizing the business-to-customer approach. This system will streamline the sales process and aid in managing sales data, encompassing product data, customer data, and transactions. The system development will utilize the PHP programming language and the MySQL database, widely employed in online development. The research methodologies encompass literature review, observation, and interviews. The chosen approach for system development is Object-Oriented Software Engineering (OOSE), which utilizes Unified Modeling Language (UML) for system modeling. This includes using various diagrams such as use case, activity, sequence, and class diagrams. Hence, the sales information system is anticipated to offer a more efficient resolution for carrying out sales procedures and enhancing data administration promptly, safely, and precisely. Implementing this strategy will enable the fashion store to expand its consumer base, particularly among individuals located beyond the geographical reach of the actual store, thereby improving overall business performance.